1995
DOI: 10.1161/01.cir.91.2.270
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Variant at the Angiotensin-Converting Enzyme Gene Locus Associates With Coronary Artery Disease in the Caerphilly Heart Study

Abstract: The DD genotype is a linkage marker for an etiologic mutation at or near the ACE gene that may confer risk of CAD detectable in subjects previously unidentifiable with "classic" risk factors. However, this risk may be quantitatively small among the general male population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 35 publications
5
79
1
Order By: Relevance
“…12 Since that time a lot of studies were performed in which ACE genotype was used as a tool, through association studies, to investigate the role of tissue ACE in human disease pathogenesis. [13][14][15][16][17] Taken together, the available evidence supports the notion that the DD ACE genotype adversely influences specific cardiovascular diseases but appears to do so in specific geographical areas and in particular patient subgroups. 18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED.…”
Section: Introductionsupporting
confidence: 62%
“…12 Since that time a lot of studies were performed in which ACE genotype was used as a tool, through association studies, to investigate the role of tissue ACE in human disease pathogenesis. [13][14][15][16][17] Taken together, the available evidence supports the notion that the DD ACE genotype adversely influences specific cardiovascular diseases but appears to do so in specific geographical areas and in particular patient subgroups. 18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED.…”
Section: Introductionsupporting
confidence: 62%
“…4,38 In contrast, the data that support the contention that the D allele could also be a general marker of CVD are controversial. Positive studies [7][8][9][10][11][12][13][14] have in fact been contradicted not only by negative results basically for all types of CVD [15][16][17][18] (for reviews, see Koch et al 19 and Samani et al 45 ) but also by a study showing an association of the D allele with longevity in centenarians. 46 The mechanisms responsible for the supposed predisposition to developing CVD also remain largely speculative, because (1) the D/I polymorphism is located in intron 16 (ie, a noncoding region); (2) no change in the kinetic properties of ACE in relation with this polymorphism was documented 47 ; and (3) the contention that the higher ACE plasma levels associated with the D allele enhances Ang II generation in vivo 31 has been challenged.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The D allele has thereafter been associated with other CVD, including dilated and ischemic cardiomyopathy, coronary and carotid artery disease, coronary artery spasm, restenosis, left ventricular hypertrophy in hypertensives, left ventricular dysfunction, and, more recently, atherosclerotic renovascular hypertension. [7][8][9][10][11][12][13][14] However, opposite results for almost every clinical association have also been published, and therefore the value of the D/I genotyping for the purpose of cardiovascular risk stratification has been challenged [15][16][17][18][19][20][21][22][23] (for reviews, see Butler et al 24 and Agerholm-Larsen et al 25 ). Furthermore, the mechanisms by which the D allele would lead to a generalized increase in CVD risk remain largely speculative.…”
mentioning
confidence: 99%
“…These findings have also been shown in other populations, even in prospective studies. 10,11 However, not all studies have demonstrated this association. 12,13 There are few studies that have investigated the association between BMI, ACE gene I/D polymorphism and CHD.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 There are few studies that have investigated the association between BMI, ACE gene I/D polymorphism and CHD. 10,13 In Mediterranean populations in Southern Europe with a low incidence and prevalence of CHD, the commented relation has not been studied.…”
Section: Introductionmentioning
confidence: 99%